Impactos da distância institucional e do conhecimento experiencial na velocidade de internacionalização de subsidiárias estrangeiras - Chang, Rachel Xenia (2017)
Internationalization speed of multinational enterprises through foreign subsidiaries is a relevant topic on the international management literature. Its definition, however, presents conceptual differences. Some authors conceptualize internationalization speed with a onedimensional perspective, considering the difference between the year of the multinational's first performance abroad and its year of foundation. Others add to this view the subsequent entries after the first internationalization in a particular country or region. The question of how to measure the internationalization speed also does not present a consensus among different authors, as it can be related to new subsidiaries (commitment speed) and to the countries abroad (dispersion speed). Moreover, extrinsic and intrinsic aspects related to subsidiaries can influence the pace of their international expansion. This study aims to analyze the influence of institutional distances, dismembered on its regulatory, normative and cultural-cognitive pillars and experiential knowledge, subdivided into regional and global experience, into the speed of commitment and dispersion of multinational enterprises through foreign subsidiaries. For this purpose, a secondary base was used with 492 operations within electronics industries established in 46 countries. The hypotheses raised were analyzed with the use of correlations and multiple linear regressions. The results presented suggest three contributions to the academic literature. First, it is important to differentiate the speed of internationalization in terms of commitment and dispersion. Secondly, it is observed that the experiential knowledge positively moderates the relation between commitment and dispersion speed and the institutional distance. Finally, high regulatory and normative distances can be positive for the commitment speed through subsidiaries when the multinational enterprise has little international experience. Thus, this study suggests that other aspects can positively contribute to stimulate international expansion and, therefore, opens up opportunities for future contributions to the theme of internationalization speed.